Technology-Based Learning Innovation: Encouraging Literacy and Numeracy in the 21st - Erni Ratna Dewi; Ajani Restianty; Mohamad Kamil Salas; Muh Fihris Khalik (Journal of Pedagogi, 2024)
This research explores the impact of implementing technology-based learning innovations on student literacy and numeracy at SMP Negeri 1 Makassar using a qualitative approach. Data was collected through classroom observations, in-depth interviews with teachers, and focus group discussions with students. The research results show that the integration of technology, including online learning applications and educational tools, has significantly increased student engagement and made it easier for them to access learning materials. Technology also contributes to more interactive and interesting learning, and supports better understanding of the material. Although many teachers display positive attitudes towards the use of technology, some experience challenges related to inadequate training and limited infrastructure. Students, on the other hand, felt more motivated and engaged in learning after technology was implemented, with visible improvements in their literacy and numeracy scores. This research recommends improving technology infrastructure, ongoing training for teachers, and adjusting the curriculum to be more adaptive to the use of technology. These findings confirm that technology has great potential to improve educational outcomes and prepare students to face the challenges of the 21st century more effectively.